Massacre of Vilnius Jews and Vilnius Ghetto (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 2003)
The article gives a survey of the destruction of Vilnius Jews’ community, points out the most important stages in the history of Vilnius ghetto and typical features, provides statistics on victims, describes the inside structure of ghetto administration and its behavior, also activities by the anti-Nazi ghetto underground. Author of the article not only did summarize the well known literature about the genocide of Vilnius Jews, but also used less known archival materials.